Epidemia otyłości dzieci w 2. dekadzie XXI w. w Polsce i w Europie. Aspekt medyczny i aspekt ekonomiczny problematu - Nackiewicz, Jolanta; Baran, Zbigniew (Wałbrzych: Wyższa Szkoła Zarządzania i Przedsiębiorczości)
A serious health problem in contemporary space-time is the childhood obesity in the world. On the basis of population surveys of European children [from 2014], it was presented that a minimum of 4.4 million (maybe even 5.0 million) of European children were obese then.
Keywords: otyłość; otyłość dzieci; styl życia; edukacja zdrowotna; profilaktyka; obesity; children`s obesity; quality of life; health education; prevention